Enhancing Forest Fire Communication: A Case Study of Oregon Government Social Media - Setiono, Dede (Institut Pertanian Bogor (IPB University), 2024)
Forest fires pose an escalating threat, demanding effective communication strategies for communities. While past research underscores the importance of community involvement and transparent communication, the dominance of social media in today's media landscape calls for a reassessment. This study investigates the utilization of social media, specifically Facebook, by the Oregon government during the 2022 fire season in Cedar Creek and Double Creek regions. Through Facepager, 4576 posts and comments were collected and then analyzed using the multi-coder approach and Vader Algorithm focusing on post frequency, thematic content, and user sentiments. The result reveals that positive sentiment polarity scores were observed with 0.61 and 0.71 for Cedar Creek and Double Creek respectively, however, the thematic and post-frequency analysis suggests a need for government agencies to diversify content, emphasizing scientific aspects and addressing community concerns. The findings offer valuable insights for enhancing risk communication strategies, promoting informed public engagement, and guiding effective government communication in wildfire scenarios.